Design of Online Upgrade Scheme of Software of Electro-hydraulic Control System of Hydraulic Supports - XU Chun-yu; XIN Chun-hong; SONG Jian-cheng; TIAN Mu-qin; ZHANG Wen-jie; LIU Min (Gong-kuang zidonghua, 2012)
In view of problems that software upgrade of support controller and terminal controller of existed hydraulic supports needs underground technical personnel to disassemble each controller, which is time-consuming and low in efficiency, the paper proposed a design of online upgrade scheme of software of electro-hydraulic control system of hydraulic supports. It introduced system composition, changes in the code storage space and program flow for online upgrade in details, and gave experimental data and analysis. The scheme achieves remote online upgrade of support controller and terminal controller, and the upgrade process is easy and fast.